Microstructural investigation of gas shale in Longmaxi Formation, Lower Silurian, NE Sichuan Basin, China. Issue 4 (July 2017) - Sun, Shasha; Liang, Feng; Tang, Ligen; Wu, Jin; Ma, Chao
The purpose of this paper is to probe into the nature and variability in vertical microstructure within Longmaxi gas shales of well WX2, Lower Silurian, located in the NE Sichuan Basin of China. To understand the pore system of these rocks, the total porosity, pore size distribution (PSD), surface area, organic geochemistry, and mineralogy, some image analyses by electron microscopy are performed. The obtained results indicated the following. (1) Gas shales have a complex pore structure. Total porosity from helium pycnometry ranges between 0.75% and 4.62%. Total organic content ranges between 3.4 wt.% and 11 wt.%, and vitrinite reflectance measured between 2.5% and 3.1%. The gas shales are quartz and clay rich. (2) Focused ion beam milling and field emission scanning electron microscopy provide high-resolution images of pores distribution and types. Three primary types of pores, organic matter (OM)-hosted pores, mineral-hosted pores, and micro-fractures, and 11 subgroups have been recognized. (3) The N2 isotherm curves are grouped into two types, II b as well as IV a, with the hysteresis loop belonging to Type B, reflecting the morphology of slits pores, and Type A, presenting cylinder pores. Combination of N2 and CO2 isotherm curve shows bimodal in two diameter sections, 0.3–1 nm and 2–5 nm, revealing meso-pores play important role in pore volume, whereas the micro-pores have great influence on pore specific surface area. (4) Total organic carbon (TOC) is considered to be the dominant contributor to total porosity and pore types, with the proportion of OM-hosted pores following the upward decreasing tendency of TOC. In plane, pore types are controlled by sedimentary facies. The OM-hosted pores are more prevalent in deep shelf facies within lower part of shale other than upper formation, instead of shallow shelf facies.